Effect of fully immersive virtual reality treatment combined with exercise in fibromyalgia patients: a randomized controlled trial - Gulsen, C.; Soke, F.; Eldemir, K.; Apaydin, Y.; Ozkul, C.; Guclu-Gunduz, A.; Akcali, D. T. (Assistive technology, 2022)
This trial was designed to evaluate the effects of fully immersive virtual reality (IVR) treatment combined with exercise training in fibromyalgia patients. Twenty patients were randomized into exercise group (EG) or IVR combined with exercise group (Exercise+IVR). The EG had combined exercise training consisted of 30 minutes of aerobic training and 30 minutes of Pilates training and Exercise+IVR group had the same protocol with EG plus 20 minutes of IVR, twice a week for 8 weeks. Visual analogue scale for pain, Modified Sensory Organization Test for balance, Tampa Scale of Kinesiophobia for kinesiophobia, Fibromyalgia Impact Questionnaire for impact of fibromyalgia, Fatigue Severity Scale for fatigue, International Physical Activity Questionnaire for level of physical activity, six-minute walk test for functional capacity, and Short-Form 36 Health Survey for quality of life were used for evaluation. Pain, balance, kinesiophobia, impact of fibromyalgia, fatigue, level of physical activity, functional exercise capacity and quality of life scores improved significantly in both groups (p < .05). Exercise+IVR group showed significant improvement compared to the EG regarding pain, kinesiophobia, fatigue, level of physical activity, and mental component of quality of life (p < .05). IVR treatment may be an effective method as an adjunctive therapy with other exercise trainings in fibromyalgia.